Lucrèce et les sciences de la vie - Schrijvers, P. H. (Mnemosyne, Supplements, 1999)
This volume contains a collection of 11 studies on the philosophical and scientific background of Lucretius' De rerum natura . The studies 1-7 form a running commentary on the history of ideas in Drn . 5.780-1160 (Lucretius' famous description of the History of Human Mankind); 8-10 discuss some topics from book 4 (sleep, dreams, optical illusions) in relationship to other philosophical doctrines and ancient medical thought; the last study (11) treats the use of analogy by Lucretius.